Prediction of Oil Content in Fresh Palm Fruit based on an Ultrasonic Technique - Suwannarat, Sutthawee; Khaorapapong , Thanate; Chongcheawchamnan, Mitchai (Agriculture and Natural Resources, 2012)
An ultrasonic technique was proposed to predict the oil content in fresh palm fruit by measuring the attenuation based on the ultrasonic transmission mode. Several palm fruit samples with known oil content determined by Soxhlet extraction (ISO9001:2008) were tested using ultrasonic measurement. Amplitude attenuation data results for all palm samples were collected. The Feedforward Neural Network (FFN) technique was proposed to apply to predict the oil content of the samples. The root mean square error and mean absolute error of the FNN model for predicting the oil content percentage were 5.8672 and 3.4731, respectively, with a correlation coefﬁ cient of 0.8891.